Design of Ionic Liquids for Fluorinated Gas Absorption - Sosa, Júlio E. (2022)
Funding Information: This work was also supported by Associate Laboratory for Green Chemistry–LAQV, financed by national funds from FCT/MCTES (UID/QUI/50006/2020), the contracts of Individual Call to Scientific Employment Stimulus 2020.00835.CEECIND (J.M.M.A.)/2021.01432.CEECIND (A.B.P.) and by FCT/MCTES (Portugal) through the project PTDC/EQU-EQU/29737/2017. The authors thank Solvay for providing the ionic liquid tri(butyl) ethylphosphonium diethylphosphate. M.C.G. and J.A. thank IDEX-LYON for financial support (Programme Investissement d’Avenir ANR-16-IDEX-0005). Publisher Copyright: © 2022 American Chemical Society. All rights reserved.